Bioconversion of Alpha-Cembratriene-4,6-diol into High-Value Compound Farnesal Through Employment of a Novel Stenotrophomonas maltophilia H3-1 Strain - Shen Huang; Jiaming Cheng; Huibo Hu; Aamir Rasool; Robina Manzoor; Duobin Mao (Molecules)
Alpha-cembratriene-4,6-diol (α-CBT-diol) is a complex diterpenoid primarily found in Solanaceae (i.e., tobacco leaves), Pinaceae, and marine corals. Due to its intricate chemical structure, it serves as a precursor for several aroma compounds, including farnesal. Farnesal and its derivatives have applications across various fields, such as the fragrance and flavor industry, pharmaceuticals, agriculture, and cosmetics. In this study, Stenotrophomonas maltophilia H3-1, a strain capable of efficiently biodegrading α-CBT-diol into farnesal, was isolated from soil and identified through 16S rDNA sequence analysis. S. maltophilia H3-1 biodegraded 93.3% of α-CBT-diol (300 mg/L) within 36 h when grown under optimized culture conditions, including a temperature of 40 °C, pH of 8, 2 g/L maltose, and 2 g/L ammonium sulfate. Theoretically, this strain can produce 201 mg/L of farnesal during the biotransformation of α-CBT-diol. The putative α-CBT-diol bioconversion pathway expressed in S. maltophilia H3-1 is also proposed. This is the first study to report the bioconversion of α-CBT-diol into the high-value compound farnesal using a novel S. maltophilia H3-1 strain. It highlights that other compounds found in tobacco can also be bioconverted into valuable products.